PENGARUH WAKTU FERMENTASI TERHADAP KADAR PROTEIN DAN DAYA TERIMA TEMPE DARI BIJI KARET (Hevea brasiliensis) SEBAGAI SUMBER BELAJAR BIOLOGI SMA PADA MATERI BIOTEKNOLOGI PANGAN - Febri Kusnanto; Agus Susanto; HRA Mulyani (Bioedukasi Jurnal Pendidikan Biologi, 2013)
The purposes of this study were 1) To determine the variation of which produces the best tempe manufacture of rubber seeds. 2) To determine the effect of fermentation on protein content in soybean seeds produced rubber. 3) To determine the effect of fermentation on the quality of flavor, color, odor, and texture of tempeh rubber seeds produced by organoleptic tests. 4) To determine the effect of fermentation on the application of research and the protein content of soybean seeds receive the rubber as the source of the material studied biology at the Food Biotechnology. Data results showed that the fermentation of soybean protein affect the levels of rubber seed (Hevea brasiliensis) is seen with Fhit (5.5147)> Ftab 5% (4.07) and test results of the Real Honest Differences (BNJ) to the protein content of soybean seeds rubber (Hevea brasiliensis) show that the treatment time of 36 h fermentation significantly different from treatment of 60 hours and 72 hours. The treatment time of 36 hours of fermentation produces the highest protein levels by an average of 8.5939%.       Kata kunci: Waktu fermentasi, kadar protein tempe, daya terima.